Mecanismos para fortalecer la carrera judicial en Michoacán - Piña Martínez, Karla Teresa (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The Judiciary as a constitutionally developed entity, has been increasing its functions and powers in modern times, taking as a reference that emerged as a depository of state power to resolve and resolve constitutional controversies, therefore it is relevant to touch not only the birth, but the Improvement of the Judiciary through the different stages of Mexican constitutionalism, where the important task of imparting justice emerges, taking into account that there is currently a relationship of powers, but not a balance between them. It is through its legal framework that there have been restructurings or reforms in the field of the judiciary, endowing it with administrative bodies such as the Federal Judicial Council to give greater freedom and independence to the applicators of the law, as the body in charge of administration, Supervision and discipline of the Judiciary of the Federation, being governed under the guiding principles of judicial autonomy, the right of a prompt, complete and impartial justice to those who are responsible for imparting justice under the guiding principle of the Judicial Career, whose main function is The selection, preparation and professionalization of those who are part of the Judicial Branch of the Federation, and the importance of its auxiliary bodies such as the Federal Judicature Institute, whose purpose is specialized judicial education through academic programs with the aim that aspirants Gain better knowledge, skills, For the proper performance of the judicial function, with the responsibility to improve the constitutional functions that the Judiciary itself has in commendations.

El Poder Judicial como ente constitucionalmente desarrollado, ha venido incrementando sus funciones y facultades en los tiempos modernos, tomando como referencia que surgió como depositario de la potestad estatal para dirimir y solucionar controversias constitucionales, por ello es relevante tocar no solo el nacimiento, sino el perfeccionamiento del Poder Judicial a través de las diferentes etapas del constitucionalismo mexicano, en donde emerge la importante labor de impartir justicia, tomando en cuenta que actualmente existe una relación de poderes, más no un equilibrio entre estos. Es a través de su marco jurídico que han surgido reestructuras o reformas en el ámbito de la judicatura, dotándolo de órganos administrativos como el Consejo de la Judicatura Federal para dar mayor libertad e independencia a los aplicadores del derecho, como órgano encargado de la administración, vigilancia y disciplina del Poder Judicial de la Federación, rigiéndose bajo los principios rectores de autonomía judicial, derecho de una justicia pronta, completa e imparcial a quienes son los encargados de impartir justicia bajo el principio rector de la Carrera Judicial, cuya principal función se encuentra la selección, preparación y profesionalización de quienes integran el Poder Judicial de la Federación, y la importancia de sus órganos auxiliares como el Instituto de la Judicatura Federal, cuya finalidad es la enseñanza judicial especializada a través de programas académicos con el objetivo de que los aspirantes obtengan mejores conocimientos, habilidades, destrezas para el adecuado desempeño de la función judicial, con la responsabilidad de mejorar las funciones constitucionales que el propio Poder Judicial tiene en comendadas.
Facultad de Derecho y Ciencias Sociales. Especialidad en Derecho procesal
Keywords: info:eu-repo/classification/cti/5; FDCS-E-2017-1276; Tesina; Poder judicial; Consejo de la Judicatura; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/875